Komersialisasi Keterlambatan dalam Ekosistem Paylater: Komparasi Time Value of Money dan Larangan Riba al-Jahiliyyah pada Denda Otomatis - Nahdhif Rivano; Ari Maskuri; Satria Finto Saputra; Budi Jaya Putra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This article dissects how payment delay within the paylater (Buy Now, Pay Later) ecosystem shifts in function, from a mere credit-risk event into a commercialised revenue stream generated through automated late-fee algorithms. Employing a qualitative approach with a descriptive-critical method and comparative conceptual analysis, the study confronts two epistemologically opposed paradigms, namely the conventional doctrine of the Time Value of Money and the prohibition of riba al-jahiliyyah in Islamic economic law. Secondary data from the peer-to-peer lending fintech industry of the Special Region of Yogyakarta for 2024 to 2025 serve as an empirical proxy, revealing a rise in loan outstanding from IDR 949 billion to IDR 1,363 billion alongside a persistently fluctuating ninety-day default rate (TWP 90) that peaked at 3.31 percent in the second quarter of 2025. The findings indicate that within the conventional framework this default figure becomes fuel for the snowballing late-fee mechanism, whereas the sharia framework, through the instruments of gharamah and ta'wid, separates the disciplining function from the profit function and distinguishes the mu'sir debtor from the mamtul. The article concludes that the commercialisation of delay contradicts the maqasid of hifz al-mal and recommends reallocating late-fee cash flows to social funds as an instrument of consumer protection.